Phytochemical Analysis and HPTLC Screening with Quantification of Bioactive Compounds in Cassia fistula for Pharmaceutical Applications - Sonali V. Dhamal; Jayant C. Thorat (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim: The goal of this study involves thorough identification and measurement of bioactive compounds in Cassia fistula pods ethanolic extract through High-Performance Thin-Layer Chromatography (HPTLC). Study Design: An experimental investigation of Cassia fistula pods ethanolic extract through phytochemical screening and HPTLC analysis took place. Place and Duration of Study: These experiments were performed at the Department of Pharmacognosy within BharatiVidyapeeth's structures during the six-month duration. Methodology: The preliminary phytochemical screening tested crude ethanolic extracts of Cassia fistula pods to identify alkaloids, flavonoids, phenols along with tannins as secondary metabolites. The research team used HPTLC to perform structured analysis for identifying main bioactive components in the investigated samples and to measure the levels of flavonoids along with phenolic acids specifically. Results: The phytochemical analysis showed that the plant contains important secondary metabolites. The results from HPTLC analysis showed high contents of flavonoids and phenolic acids that have documented both antioxidant and anti-inflammatory properties. Conclusion: The scientific study reveals that Cassia fistula contains abundant bioactive components which makes it interesting for usage in pharmaceutical research and biomedical applications. Scientists should continue studies regarding the individual determination and structural definition of compounds to establish new therapeutic entities.